Bronchiolectasis-a complication of artificial ventilation. Issue 6346 (2nd October 1982) - Slavin, G; Nunn, J F; Crow, J; Doré, C J
Abstract : Pulmonary barotrauma associated with artificial ventilation is recognised clinically as pneumothorax, pneumo-mediastinum, or subcutaneous emphysema. Eleven patients who died in the intensive therapy unit after artificial ventilation were found at necropsy to have pronounced bronchiolectasis, which was associated with a greatly increased physiological dead space during life. The condition was best predicted by the maximum level of positive end expiratory pressure and the duration of application of positive end expiratory pressure. The clinical course of the lesion in survivors is not known. Further detailed studies are needed, but it is suggested that high levels of positive end expiratory pressure should be used with caution.